Update on diagnostic tests for human immunodeficiency virus infection in pregnant women - Álvarez-Carrasco, Ricardo (2024)
Early diagnosis and proper interpretation of tests to diagnose humanimmunodeficiency virus (HIV) infection are of great importance during pregnancy.It is necessary to know the characteristics of such tests in order to make timelyand correct decisions. The aim of this article is to disseminate the perception andinterrelation of the outcomes of these tests currently used and their organization inthe national diagnostic algorithm.